GENDER DAN KEWIRAUSAHAAN (STUDI SOSIAL EKONOMI MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM ANGKATAN 2019 UIN MATARAM) - Hesti Gustriliani; Baiq El Badriati; Nurul Susianti (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2023)
This research is motivated by how gender and entrepreneurship (a study on the socio-economy of students of the Faculty of Economics and Islamic Business Class of 2019 UIN Mataram) where students run a business during college to increase their income, but each gender character is different in managing their business. Therefore, researchers want to examine: (1) the role of each gender character in student business success, (2) the role of socio-economic conditions in student business success. This type of research is qualitative research using a descriptive qualitative approach. The data collection methods used are observation, interviews and documentation. The research instrument used a structured interview. While the data analysis techniques used by researchers are such as: data reduction, data presentation, conclusion drawing and verification. The object of this research is students who have a business at the Faculty of Economics and Islamic Business, 2019 UIN Mataram. The results of this study indicate that the character of each gender has a role in student businesses, there are no significant differences between male and female students in managing their businesses and socio-economic conditions play an active role in the success of student businesses.